Kelas Ibu Hamil Bernuansa Islami dalam Upaya Meningkatkan Kesehatan Ibu dan Janin: Islamic Class for Pregnant Women in an Effort to Improve Maternal and Fetal Health - Dewi Andariya Ningsih; Umi Nur Kholifah; Susiana Susiana; Silaturrohmih Silaturrohmih; Siti Hilmi Musyarrofah; Siti Nurhidayati (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The increasing number of reproductive ages undergoing pregnancy becomes important to pay attention to the health of the mother and fetus so that there is a need for class activities for pregnant women with Islamic nuances. This activity aims to improve the knowledge and skills of pregnant women in the fields of pregnancy, antenatal care, childbirth, postpartum care, baby care, myths, infectious diseases and birth certificates. The target is all pregnant women in Sumberejo village. The expected benefits of class activities for pregnant women include increasing knowledge and skills of mothers from prenatal care to baby care, and building friendships between pregnant women. women and health professionals. It is included. The method used in this activity consists of brainstorming, lectures, video screenings, and demonstrations. In each meeting, Islamic information is affixed regarding the theme raised at each meeting. Participants in the activity are all pregnant women, a maximum of 10 people in each implementation. Speakers at the event included a team of village midwives, students, and a team of lecturers from the Midwifery Faculty of Health Sciences, Ibrahimy University. The results of these activities include all pregnant women who attended the event, it can be seen from the attendance sheet and active pregnant women in the meeting. ABSTRAK Semakin banyaknya usia reproduktif menjalani masa kehamilan menjadi penting untuk memperhatikan kesejahteraan kesehatan ibu dan janin sehingga diperlukan adanya kegiatan kelas ibu hamil yang bernuansa Islami. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan keterampilan ibu hamil di bidang kehamilan, pemeriksaan kehamilan, persalinan, perawatan nifas, perawatan bayi, mitos, penyakit menular dan akta kelahiran. Sasarannya adalah seluruh ibu hamil di desa Sumberejo. Manfaat yang diharapkan dari kegiatan kelas ibu hamil antara lain meningkatkan pengetahuan dan keterampilan ibu dari perawatan prenatal hingga perawatan bayi, dan membangun persahabatan antar ibu hamil. wanita dan profesional kesehatan. Hal ini disertakan. Metode yang digunakan dalam kegiatan ini terdiri dari brainstorming, ceramah, pemutaran video, dan demonstrasi. Disetiap pertemuan di bubuhkan informasi islami terkait tema yang diangkat di setiap pertemuannya. Peserta kegiatan seluruh ibu hamil maksimal 10 rang disetiap pelaksanaan. Pembicara dalam acara tersebut antara lain tim bidan desa, mahasiswa, dan tim dosen Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy. Hasil dari kegiatan tersebut meliputi seluruh ibu hamil yang hadir pada acara tersebut, terlihat dari lembar kehadiran dan ibu hamil aktif dalam pertemuan tersebut.